Brahma Related Gene 1 (Brg1) Regulates Cellular Cholesterol Synthesis by Acting as a Co-factor for SREBP2 - Fan, Zhiwen; Kong, Ming; Li, Min; Hong, Wenxuan; Fan, Xiangshan; Xu, Yong (Frontiers in Cell and Developmental Biology, 2020)
Hepatocyte is a hub for cholesterol metabolism. Augmented synthesis of cholesterol in the liver is associated with hypercholesterolemia and contributes to the pathogenesis of a host of cardiovascular and metabolic diseases. Sterol response element binding protein 2 (SREBP2) regulates hepatic cholesterol metabolism by activating the transcription of rate-limiting enzymes in the cholesterol biosynthesis pathway. The underlying epigenetic mechanism is not well understood. We report here that mice with hepatocyte-specific knockout (CKO) of Brg1, a chromatin remodelling protein, exhibit reduced levels of hepatic cholesterol compared to the wild type (WT) littermates when placed on a high-fact diet (HFD) or a methionine-and-choline-deficient diet (MCD). Down-regulation of cholesterol levels as a result of BRG1 deficiency was accompanied by attenuation of cholesterogenic gene transcription. Likewise, BRG1 knockdown in hepatocytes markedly suppressed the induction of cholesterogenic genes by lipid depletion formulas. Brg1 interacted with SREBP2 and was recruited by SREBP2 to the cholesterogenic gene promoters. Reciprocally, Brg1 deficiency dampened the occupancies of SREBP2 on target promoters likely through modulating H3K9 methylation on the cholesterogenic gene promoters. Mechanistically, Brg1 recruits the H3K9 methyltransferase KDM3A to co-regulate pro-cholesterogenic transcription. KDM3A silencing dampened the cholesterogenic response in hepatocytes equivalent to Brg1 deficiency. In conclusion, our data demonstrate a novel epigenetic pathway that contributes to SREBP2-dependent cholesterol synthesis in hepatocytes.